DEVELOPMENT OF CLEAN WATER DISTRIBUTION NETWORK SYSTEM IN GENTENG SUB-DISTRICT BANYUWANGI USING EPANET 2.0 PROGRAM - Ayu Rahmad Jayanti; Ririn Endah Badriani; Yeny Dhokhikah (Universitas Jember, 2019)
The clean water distribution in the Genteng Subdistrict, Banyuwangi Regency is included in the service area of the Zone 1 PDAM tile unit. The 60 liters/second reservoir discharge capacity is obtained from Sumber Umbul Sari in the Glenmore District. The distribution of clean water in Zone 1 is still less than 70% of the area served, as the installed discharge capacity is estimated to be insufficient. In order to achieve the distribution goal, a network system must be developed by adding direct debits and planning a new pipeline. The Epanet 2.0 program simplifies the calculation of pipeline networks by integrating elevation data, network maps, pipeline specification, and load. The analysis of the simulation results was conducted using the Public Works Minister's hydraulic parameter standards 2007. Planning of a distribution network and a cost budget in 2029 were done to estimate the water supply needs and budgets required. The hydraulic simulation results based on the analysis of the pressure of all joints are in accordance with the standard, while the analysis of the velocity in pipe is less standard. The need for water discharge in 2029 is 71.6 liters/second. In Kembiritan Village, the construction of distribution pipes with an additional reservoir unit was planned. The planned pipe dimensions in the development area were 25 mm at 796 meters, 50 mm at 4062 meters, and 75 mm at 1518 meters. The cost of planning a clean water distribution system in 2029 is Rp. 1,431,375,000.00. Distribusi air bersih di Kecamatan Genteng Kabupaten Banyuwangi merupakan wilayah pelayanan Zona 1 PDAM unit Genteng. Kapasitas debit reservoir sebesar 60 liter/detik berasal dari sumber umbul sari di Kecamatan Glenmore. Pendistribusian air bersih di wilayah Zona 1 masih kurang dari 70% wilayah yang terlayani, karena diperkirakan kapasitas debit yang terpasang kurang mencukupi. Untuk memenuhi target pemerataan distribusi perlu pengembangan sistem jaringan dengan penambahan debit dan perencanaan jaringan pipa baru. Program Epanet 2.0 memudahkan dalam perhitungan jaringan perpipaan dengan mengintegrasi data elevasi, peta jaringan, spesifikasi pipa dan debit. Analisis hasil simulasi menggunakan standar parameter hidrolis Permen PU 2007. Perencanaan pengembangan jaringan distribusi dan anggaran biaya pada tahun 2029 guna memperkirakan debit kebutuhan air dan anggaran biaya yang dibutuhkan. Hasil simulasi hidrolis berdasarkan analisis tekanan semua junction telah sesuai standar, sedangkan analisis kecepatan masih di bawah standar. Kebutuhan debit air tahun 2029 sebesar 71,6 Liter/detik. Pengembangan pipa distribusi direncanakan di Desa Kembiritan dengan tambahan satu unit reservoir. Dimensi pipa rencana di wilayah pengembangan digunakan diameter 25 mm sepanjang 796 m, diameter 50 mm sepanjang 4062 m dan diameter 75 mm sepanjang 1518 m. Biaya perencanaan sistem distribusi air bersih tahun 2029 sebesar Rp. 1.431.375.000,00.